Spontaneous Bacterial Empyema - An Underdiagnosed Complication of Hepatic Hydrothorax (Archives of Clinical and Medical Case Reports, 2021)
Spontaneous bacterial empyema (SBEM) is a life-threatening and underdiagnosed development of hepatic hydrothorax (HH), which is a significant complication of liver cirrhosis and portal hypertension. SBEM is the development of a spontaneous infectious process in a pre-existing pleural effusion without any evidence of pneumonia in patients with Hepatic Hydrothorax. Patients with SBEM has poor prognosis with significantly high rate of mortality and morbidity. We present the case of a 54-year-old female with history of decompensated liver cirrhosis secondary to alcohol use disorder, recurrent ascites, refractory bilateral pleural effusions who had developed SBEM associated with uncharacteristically high glycopleuria values. In this article, we will emphasize on recent data focusing on the diagnostic complications and treatment of cirrhotic patients with SBEM. Increased awareness of this uncommon condition will help clinicians recognize and address it early.